Anxiety and Sleep Problems of College Students During the Outbreak of COVID-19 - Wang, Xing; Chen, Hongguang; Liu, Ling; Liu, Yuan; Zhang, Nan; Sun, Zhenghai; Lou, Qing; Ge, Weichun; Hu, Bo; Li, Mengqian (Frontiers in Psychiatry, 2020)
This study aimed to explore the psychological situation and the influence of the outbreak of COVID-19 on college students. An online questionnaire survey was conducted among 3,092 Chinese college students who were quarantined at home as a result of the COVID-19 pandemic. The survey tools included the Generalized Anxiety Disorder 7-Item Scale (GAD-7), the Perceived Stress Scale (PSS-10), and the Self-Rating Scale of Sleep (SRSS). Of all the respondents, the prevalence of anxiety symptoms, sleep problems, any of the two, and both of the two, were 16.8, 13.5, 25.1, and 5.3%, respectively. Of the participants, 43.7% of the college students had higher perceived stress. Factors associated with anxiety symptoms included reading the daily news with higher frequency (1–3 times; 4–7 times; more than 7 times), having sleep problems, higher stress, and carelessness with the number of remaining masks. Factors associated with sleep problems included postgraduates, reading the news with higher frequency daily (1–3 times), the frequency of going out per week (1–3 times), having anxiety symptoms and higher stress. Factors associated with higher perceived stress included reading the daily news with higher frequency (4–7 times), anxiety about the number of remaining masks (1–10; more than 20), having anxiety symptoms, and having sleep problems. The prevalence of anxiety symptoms, sleep problems, and higher perceived stress among college students was high during the COVID-19 outbreak. Particular attention should be paid to psychological support for college students quarantined at home, especially those at high risk of psychological problems.